2020
DOI: 10.9734/ejnfs/2020/v12i1230336
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiogram of Salmonella Species Isolated from Snail (Archachatina marginata) Sold in Port Harcourt, Rivers State, Nigeria

Abstract: Increase in microbial population especially Salmonella species in food due to improper handling, storage and exposure to contaminants can raise public health concerns when consumed without adequate processing. This study evaluates the prevalence and antibiogram of Salmonella species associated with the giant land Snail (Archachatina marginata) sold in markets around Port Harcourt metropolis. A total number of seventy two (72) samples of land snail were collected from three markets; Creek Road, Mile one and Rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…However, a 72.7 % (n=40), 16.4 % (n=9) and 25.4% (n=14) Salmonella susceptibility was recorded across the markets for nitrofurantoin (NIT), gentamycin (GEN) and cefixime (CXM), respectively. The total sensitivity of Salmonella to ciprofloxacin and ofloxacin recorded in the present study is in agreement with the 100% resistance reported by Daminabo et al, (2020) Five (5) Salmonella species produced the expected 620bp and 284bp against fliC and invA genes, respectively representing 9.1 % occurrence of both genes among Salmonella isolated from raw and ready-to eat snails. However, none of the Salmonella isolated produced bands against sefA gene conferring resistance to any of the antibiotics tested.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, a 72.7 % (n=40), 16.4 % (n=9) and 25.4% (n=14) Salmonella susceptibility was recorded across the markets for nitrofurantoin (NIT), gentamycin (GEN) and cefixime (CXM), respectively. The total sensitivity of Salmonella to ciprofloxacin and ofloxacin recorded in the present study is in agreement with the 100% resistance reported by Daminabo et al, (2020) Five (5) Salmonella species produced the expected 620bp and 284bp against fliC and invA genes, respectively representing 9.1 % occurrence of both genes among Salmonella isolated from raw and ready-to eat snails. However, none of the Salmonella isolated produced bands against sefA gene conferring resistance to any of the antibiotics tested.…”
Section: Discussionsupporting
confidence: 91%
“…The Salmonella counts of raw snail ranged from 3.32 to 5.04 log10CFU/g, 4.04 to 6.04 log10CFU/g and 4.71 to 6.67 log10CFU/g, from samples purchased from Choba, Rumuokoro and Oyigbo, respectively. Findings in the present study are comparable to the counts, ranging from 2.91±3.19 to 7.39±0.45 log10CFU/g and 0.4 to 3.56 log10CFU/g reported by Nyoagbe et al (2016) and Daminabo et al (2020) in raw snails sold in markets and breeding farms in Greater Accra Region and markets across Port Harcourt, respectively. Differences may be attributed to differences in the farms from which the snails were purchased by the traders, since snails feed on debris.…”
Section: Discussionsupporting
confidence: 88%